Binding of the phage display derived peptide CaIX-P1 on human colorectal carcinoma cells correlates with the expression of carbonic anhydrase IX - Askoxylakis, Vasileios; Ehemann, Volker; Rana, Shoaib; Krämer, Susanne; Rahbari, Nuh Nabi; Debus, Jürgen; Haberkorn, Uwe (International journal of molecular sciences, 2012)
Phage display represents an attractive screening strategy for the identification of novel, specific binding ligands that could be used for tumor targeting. Recently, a new peptide (CaIX-P1) with affinity for human carbonic anhydrase IX (CAIX) was identified and evaluated. The aim of the present study is to characterize the properties of CaIX-P1 for targeting human colorectal carcinoma and investigate the correlation of peptide binding with the expression of carbonic anhydrase IX. Human colorectal carcinoma HCT116 and HT29 cells were investigated for CAIX expression using Western Blot analysis. Binding and competition studies of 125I-radiolabeled CaIX-P1 were performed on HCT116 cells in vitro. FACS analysis and fluorescence microscopy studies were carried out after cell incubation with fluorescein-labeled CaIX-P1 and rhodamine-labeled anti-human CAIX-mAb. Our studies revealed an enhanced in vitro expression of carbonic anhydrase IX in HCT116 and HT29 cells with increasing cell density. Binding of 125I-labeled-CaIX-P1 on HCT116 cells increased with increasing cell density and correlated to the CAIX expression. FACS analysis demonstrated a correlation of cell labeling between FITC-CaIX-P1 and rhodamine-labeled anti-CAIX-mAb in both HCT116 and HT29 cells. The results of our study indicate that the phage display identified peptide CaIX-P1 might be an attractive candidate for the development of a ligand targeting CAIX in colorectal cancer.
Gesehen am 15.08.2018